Hypertension and the development of new onset chronic kidney disease over a 10 year period: a retrospective cohort study in a primary care setting in Malaysia - Chia, Y.C.; Ching, S.M. (BioMed Central, 2012)
Background: Little is known about the rate of progression to chronic kidney disease (CKD) among hypertensive patients, particularly at the primary care level. Methods: This study aims to examine risk factors associated with new onset CKD among hypertensive patients attending a primary care clinic.This is a 10-year retrospective cohort study of 460 patients with hypertension who were on treatment. Patient information was collected from patient records. CKD was defined as a glomerular filtration rate <60 ml/min per 1.73 m² (Cockcroft-Gault equation). Multiple logistic regression statistics was used to test the association in newly diagnosed CKD. Results: The incidence of new CKD was 30.9% (n = 142) with an annual rate of 3%. In multivariate logistic regression analysis, factors associated with development of new onset of CKD among hypertensive patients were older age (odds ratio [OR] 1.123, 95% confidence interval [CI] 1.078-1.169), presence of diabetes (OR 2.621, 95% CI 1.490-4.608), lower baseline eGFR(OR 1.041, 95% CI 0.943-0.979) and baseline hyperuricaemia (OR 1.004, 95% CI 1.001-1.007). Conclusions: The progression to new onset CKD is high among urban multiethnic hypertensive patients in a primary care population. Hence every effort is needed to detect the presence of new onset CKD earlier. Hypertensive patients who are older, with underlying diabetes, hyperuricaemia and lower baseline eGFR are associated with the development of CKD in this population.